Enhancing critical thinking in Indonesian high school physics with physbook-powered problem-based learning - Prahani, Binar Kurnia; Saphira, Hanandita Veda; Hariyono, Eko; Wibowo, Firmanul Catur; Bunyamin, Muhammad Abd Hadi (Journal of Turkish Science Education, 2026)
To align with Assessment and Teaching of 21st-Century Skills (ATC21S), especially in the area of Critical Thinking Skills (CTS), it is crucial to embrace educational innovations that depart from traditional approaches and to incorporate technological advancements into the educational process. This study seeks to (1) elucidate how the PBL model, with the support of PHysBook, is employed to enhance students' CTS, (2) delineate the enhancements in students' CTS resulting from the implementation of the PBL model with PHysBook assistance, and (3) characterize the student responses following the adoption of the PBL model supported by PHysBook to boost learners' CTS. This research follows a true experimental design with randomly assigned subject control groups and pre-test and post-test evaluations. The study encompassed 140 tenth-grade high school students, with a sample size of 104 students.  The assessment of student activity in the control class has sufficient categories—the value of observation of student activities on CTS in the high category. There is a difference between O1 and O2 in class with the PBL model assisted by PHysBook in improving CTS with an increased rate in the high category with strong effect scores. The incorporation of PBL learning with PHysBook assistance to enhance CTS garnered positive feedback from students, making it a valuable innovation in the realm of education. In light of the study's limitations, it is recommended that future researchers explore similar investigations in different educational institutions or at various academic levels to compare the outcomes of CTS improvement.
Keywords: Digital learning environment; digitalisation; education; quality learning; teaching